The effect of resveratrol on the relationship of antioxidant activity and beta-hematin inhibition as an antimalarial action target - Faizal Hermanto; Fahmy Ahsanul Haq; Roikhatul Khasanah (Journal of Advanced Pharmaceutical Technology & Research)
Resveratrol is a flavonoid with numerous properties, including antioxidative, anti-inflammatory, anticancer, antimalarial, antidiabetes mellitus, and immunomodulatory effects. In the case of malaria infections, which induce oxidative stress and can lead to various complications, simply administering antimalarials is often insufficient. Therefore, adjuvant therapy, such as antioxidants, is also necessary. Resveratrol exhibits potential as an antimalarial compound and has been reported to demonstrate both in vivo and in vitro antimalarial activity. This study aims to assess the relationship between resveratrol’s antioxidant activity and its inhibition of β-hematin. The antioxidant activity was tested using the 2, 2-diphenyl-1-picrylhydrazyl method, while the β-hematin inhibition assay followed the method outlined by Huy etal. A correlation test was conducted to evaluate the connection between the β-hematin inhibition assay and antioxidant activity. The results demonstrate a strong correlation between antioxidant activity and β-hematin inhibition, with an R = 0.9841 and a P = 0.004. Both of these activities in resveratrol are highly correlated and hold significant potential in the treatment of malaria.